Desain Interior Perpustakaan sebagai Pendukung Kenyamanan pada Ruang Koleksi Anak - Ariska Idamayanti (Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2024)
This research uses a literature review method which involves searching, selecting and analyzing relevant literature from electronic databases such as Google Scholar and JSTOR. This research focused on the keywords